Peran Ibu Rumah Tangga Nelayan Dalam Meningkatkan Pendapatan Keluarga di Kelurahan Sei Merbau Kecamatan Teluk Nibung Kota Tanjungbalai. - Mbina Pinem; Rayhan Utami (Universitas Negeri Medan, 2021)
This study aims to determine: (1) The productive role of fishermen housewives in increasing family income in Sei Merbau Village, Teluk Nibung District, Tanjungbalai City, (2) The reproductive role of fishermen housewives in increasing family income in Sei Merbau Village, Teluk Nibung Kota District Tanjungbalai, and (3) The social role of fisherman housewives in increasing family income in Sei Merbau Village, Teluk Nibung District, Tanjungbalai City. This research was conducted in Sei Merbau Village, Teluk Nibung District, Tanjungbalai City in 2020. The population of this study were all fishermen housewives in Sei Merbau Village, amounting to 592 people, while the sample in this study was 10% of the total population (59 people. ) and taken using the Simple Random Sampling technique. The data collection technique is done by direct communication (interview). While the data analysis technique used is descriptive qualitative analysis techniques. The results showed that: (1) The highest productive role (48.78%) was performed by housewives who worked as factory workers, while the lowest role (21%) was performed by housewives who worked as coconut peeler. Overall, the role played by housewives of fishermen is 33.35% and is in the low category. (2) The reproductive role played by the housewives of fishermen in Kelurahan Sei Merbau, namely having dependents of 1 to 6 children. Most (57.63%) fishermen housewives had 1-2 children and a small proportion (8.47%) had 5-6 children with an average of 2-3 children. (3) In general (81.36%) fishermen housewives participated in the social activities of the unfortunate union and a small proportion (25.42%) participated in arisan activities. In addition, the recitation activity is useful for moral contributions to housewives so that they can motivate husbands to work to increase income and also motivate children to improve education. The highest role of arisan activities was 76.92% while the lowest role was 22.73%. With an average of 43.47%.